Incidence and genetic outcome of fetal choroid plexus cyst diagnosed at 18-23 weeks scan: review of case series - Olufemi Adebari Oloyede (Barpeta Obstetrics and Gynaecological Society, 2019)
Objectives: The objective of the study is to determine the incidence, clinical and ultrasound characteristics of choroid plexus cyst diagnosed during the 18 -23 weeks anomaly scan and the genetic outcome in 6 pregnancies that underwent molecular diagnosis. Methods: The information obtained from the clinical records of pregnancies with ultrasound diagnosis of choroid plexus cyst Data are analyzed and presented in simple frequency tables. Results: Choroid plexus cyst was diagnosed in 8 (0.9%) pregnancies. The majority of the cysts were solitary (75.0%), unilateral in location (62.5%) and with no associated aneuploidy marker (75.0%). Echogenic bowel and ventricular septal defect was found in 1 fetus each (25%). Six (75.0%) out of the 8 fetuses with chorionic plexus cyst had molecular diagnosis. Two (25%) were trisomy 21 and 1 was trisomy 18. Maternal age > 35 years, multiple cysts and bilateral cyst location was reported in 2 (66.7%) of the 3 fetuses with aneuploidy. Conclusions: Trisomy 21 was the more frequent aneuploidy in fetuses with choroid plexus cyst. Maternal age > 35 years, bilateral location, multiple cysts and presence of soft aneuploidy marker are suggested as indications for molecular diagnosis in CPC.